Modified reposition of the JOTEC prosthesis in the frozen elephant trunk procedure - Ghodsizad, Ali; Ungerer, Matthias; Karck, Matthias; Ruhparwar, Arjang (The heart surgery forum, 2012)
We describe a procedure in which we inserted a modified JOTEC graft following a known complication in the case of a 78-year-old male patient who underwent surgery with the frozen elephant trunk technique for an acute Stanford type A aortic dissection.
Gesehen am 07.06.2018